Children and "junk food" advertising: Critique of a recent Australian study. Issue 4 (13th June 2019) - Rossiter, John R.
Abstract: A field experiment by Australian public health researchers Norman, Kelly, McMahon, and others allegedly demonstrated that primary school children's physical health is threatened by exposure to "junk food" advertising. Their study was published in the international health journal Appetite and was clearly intended to influence government regulatory policy. The methodology of the study was taken, without acknowledgement, from an earlier American study in the Journal of Consumer Research and much other research on children's consumer behavior, including pioneering studies conducted by the present author‚ was ignored. Also, quite unforgivably, the researchers neglected to cite Australia's already strict regulatory controls on and guidelines for advertising directed to children. The present author sent a rejoinder to Appetite pointing out the many problems with Norman et al.'s research and recommending that their article be withdrawn, but the editor insisted I revise it to remove almost all the criticisms, which I naturally refused to do. Instead, by publishing this article in JCB, the present author is hoping to make consumer researchers aware of the sort of poorly performed and ideologically influenced research relating to marketing and consumer behavior that is appearing in the health journals. The present article also contributes more generally by exposing problems that must be avoided in experimental research on consumer behavior.